Ética laica de los derechos sexuales y reproductivos en el Estado constitucional - Uribe Álvarez, Roberth (2023)
For a civil society and a constitutional state, it is crucial to have a secularist movement that can separate religious ethics from the actions and decisions of the state. For a confessional state, the close association with religion can become a pa thology that interferes with constitutional rules and fundamental rights, such as the sexual and reproductive rights of individuals. The protection and exercise of these rights currently face various difficulties. Social and state secularism represents an instrument to consolidate a constitutional culture conducive to the exercise of these rights.